2018
DOI: 10.20875/makusobed.460894
|View full text |Cite
|
Sign up to set email alerts
|

Cam Tavan Sendromu: İnsan Kaynaklari Yöneti̇ci̇leri̇ Bağlaminda Bi̇r Araştirma - Glass Ceiling Syndrome: A Research in the Context of Human Resources Managers

Abstract: Bu çalışmanın amacı; cam tavan sendromunu ortaya çıkaran faktörleri tespit etmek ve cam tavanı aşma stratejilerine ilişkin insan kaynakları yöneticilerinin görüşlerini ortaya çıkarmaktır. Bu çalışmada, nitel araştırma tasarımı çerçevesinde olgu bilim (fenomenoloji) yaklaşımı benimsenmiştir. Araştırma sonuçlarına göre cam tavanın daha çok kişinin kendisinden kaynaklı bir engel olduğu, toplumsal faktörlerin etkisi olsa dahi en büyük etmenin bireysel faktörler olduğu tespit edilmiştir. Ayrıca görüşme yapılan insa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…Namely, glass ceiling beliefs increase perceptions of inequality in promotion chances. Glass ceiling beliefs bring various personal and organizational problems with it, studies conducted on this issue showed that glass ceiling beliefs lead to numerous problems, including the rise in the number of people who intends to leave, employee turnover, low level of organizational commitment (Downes et al, 2014), organizational silence (Çakıcı, 2008), organizational cynicism (Ipçioğlu et al, 2018), low level of job performance and motivation (Çetin, 2011;Aydağ, 2012) According to Moran (1992: 485), if today's organizations are to be successful in the future, they need to be transformed. In the information age, developing organizations are try out new structures (Eisler, 1991:13), such as flatter and less hierarchical.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Namely, glass ceiling beliefs increase perceptions of inequality in promotion chances. Glass ceiling beliefs bring various personal and organizational problems with it, studies conducted on this issue showed that glass ceiling beliefs lead to numerous problems, including the rise in the number of people who intends to leave, employee turnover, low level of organizational commitment (Downes et al, 2014), organizational silence (Çakıcı, 2008), organizational cynicism (Ipçioğlu et al, 2018), low level of job performance and motivation (Çetin, 2011;Aydağ, 2012) According to Moran (1992: 485), if today's organizations are to be successful in the future, they need to be transformed. In the information age, developing organizations are try out new structures (Eisler, 1991:13), such as flatter and less hierarchical.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Süreç içerisinde öğrenilmiş çaresizliğe dönüşen bu durum özellikle kadın bireylerin sosyal yenilgiyi kabullenmelerine dolayısıyla ideallerinden feragat etmelerine neden olmaktadır. Cam tavan sendromuna sebep olan çok sayıda unsur bulunmaktadır (Mattis 2004;Bharadwaj ve Nagarkoti, 2012;İpçioğlu, Eğilmez ve Şen, 2018). Bu unsurlar nitelikleri bakımından bireysel, toplumsal ve örgütsel olmak üzere üç ana tema altında sıralanmaktadır (Taşkın ve Çetin 2012).…”
Section: Cam Tavan Sendromuunclassified
“…Glass ceiling is the invisible obstacle that women face when they attempt to reach top positions in their institution (Kolade & Kehinde, 2013). In general, the glass ceiling based on prejudice and sexist approaches is an obstacle that invisible and difficult to overcome in the workplace, and it has been suggested that it have a limiting effect on women's promotion in the institution they work for (İpçioğlu, Eğilmez, & Şen, 2018). Lockwood (2004) stated that the existence of a glass ceiling can be mentioned also in an environment where individuals from a certain race or ethnic minority face obstacles to their empowerment.…”
Section: Glass Ceiling Syndromementioning
confidence: 99%
“…It is claimed that women with emotional, passive, moderate and collaborative characteristics cannot ascend to the top managerial positions due to the belief that management is a difficult task and only men with a harsh temperament can do this task (Erdirençelebi & Karakuş, 2018). In a study, 42% of the individuals working at the executive level stated that the glass ceiling syndrome was caused by the individual's lack of self-confidence (İpçioğlu, Eğilmez, & Şen, 2018). In another study, participants claimed that women's own perspectives were seen obstacles to their ascending in business life (İnandı et al, 2009).…”
Section: Individual Factorsmentioning
confidence: 99%